Evaluasi Komoditi Ekspor di Bandara Soekarno Hatta - Hartati Yusminah (WARTA ARDHIA, 2010)
Seeing of free trade in several continental markets such as of the establishment of the European Economic Community (EEC). The Asian Pacific Economy (Pasific Economy Community) NORTH America Free Trade Are (NAFTA), ASEAN Free Trade Area (AFTA), ASEAN free market with China is indirectly effect on determination of Indonesian strategy in exploting oppurtunities commodities what can penetrate the international market.With the opening of free markets Asean plus China which commenced in the year 2010 was the air transport sector has an important role in supporting efforts to increase exports, especially in the provision of adequate transport service.Soekarno Hatta airport is one of the airport that serves as the gates way of trade via air transport network, that plays an important role in supporting and smoth export and import of commodities.